Human diversity of killer cell immunoglobulin-like receptors and disease - Rajalingam, Raja (Korean Society of Hematology; Korean Society of Blood and Marrow Transplantation; Korean Society of Pediatric Hematology-Oncology; Korean Society on Thrombosis and Hemostasis, 2011)
Natural Killer (NK) cells are the third population of lymphocyte in the mononuclear cell compartment that triggers first-line of defense against viral infection and tumor transformation. Historically, NK cells were thought of as components of innate immunity based on their intrinsic ability to spontaneously kill target cells independent of HLA antigen restriction. However, it is now clear that NK cells are quite sophisticated and use a highly specific and complex target cell recognition receptor system arbitrated via a multitude of inhibitory and activating receptors. Killer cell immunoglobulin-like receptors (KIR) are the key receptors of human NK cells development and function. To date, fourteen distinct KIRs have been identified: eight are inhibitory types, and six are activating types. The number and type of KIR genes present varies substantially between individuals. Inhibitory KIRs recognize distinct motifs of polymorphic HLA class I molecules. Upon engagement of their specific HLA class I ligands, inhibitory KIR dampen NK cell reactivity. In contrast, activating KIRs are believed to stimulate NK cell reactivity when they sense their ligands (unknown). KIR and HLA gene families map to different human chromosomes (19 and 6, respectively), and their independent segregation produces a wide diversity in the number and type of inherited KIR-HLA combinations, likely contributing to overall immune competency. Consistent with this hypothesis, certain combinations of KIR-HLA variants have been correlated with susceptibility to diseases as diverse as autoimmunity, viral infections, and cancer. This review summarizes our emerging understanding of KIR-HLA diversity in human health and disease.